Efeitos do fogo nas populações de Vellozia aff. sincorana, espécie útil e endêmica da Serra do Sincorá, Bahia, Brasil - Souza, Jumara Marques (2015)
Disturbances affect plant populations in different ways, and their understanding is extremely important to define management strategies and biodiversity conservation. Such disturbances may be natural, as in the case of fire initiated by lightning, or can be anthropogenic, as the extraction of natural products. In both cases, populations of plants under interference from disturbances may increase or decrease, being necessary to understand its effects on populations in the long run. A key plant for conservation is Vellozia aff. sincorana L.B.Sm. & Ayensu (Velloziaceae), is an important species for the conservation of rupestrian fields of the western portion of the Serra do Sincorá, which is endemic. The largest area of distribution of this species, popularly know as candomba, is within the limits of the Chapada Diamantina National Park (CDNP), Bahia, Brazil, where it has a elevated cover. Candombá branches are target of extraction in the region, which are destined to ignite wood stoves. In addition to this anthropic disturbance, V. aff. sincorana is also frequently affected by fires, which despite being a natural phenomenon are largely generated by human activity in CDNP. The fire has a marked effect on V. aff. sincorana, as it stimulates their mass flowering and synchronic, with no registration of flowering in this species in the absence of fire. This study evaluated the effects of fire in individuals of V. aff. sincorana in space and stages structure and the population dynamics of this species. In addition, simulations were performed with different frequencies fire, harvest intensities, and the association of fire and harvesting in order to assess the possibilities of using fire as management tool of harvest to this species. For analyzes involving harvest, the two techniques used by candombá collectors in the region (removal of whole adult plants or branches) were simulated. For this study, individuals of V. aff. sincorana were marked, measured and monitored on 16m² plots over two censuses (2012 and 2013) in six populations, three unaffected by fire since 2008, and three affected by recent fires (2011 or 2012), approximately 40 days before the first census. In total, we monitored 1,617 individuals in 56 plots. The results showed that the recent fire affects individuals of V. aff. sincorana stimulating flowering and increases in canopy area, plant height and number of rosettes. Populations had lower rates of mortality and recruitment, however, in areas without recent fire, both the recruitment by seeds and mortality of juveniles were higher. The distribution of individuals was aggregate in all populations, averaging two individuals per m². The recent fire caused changes in distribution of individuals in class of life stages. In general, populations tended to have higher concentration of adults. The reproduction stimulus by fire increases fertility and causes growth of recent fire populations, so the recent fire encourages population increase of V. aff. sincorana, while in absence of fire populations tended to decrease. The simulation results showed that populations of V. aff. sincorana tend to decrease with increasing the gap between the fire events. In harvest simulations, the growth of population was negatively affected by the decrease in harvest intervals and no fire. The results showed that the harvesting technique of whole adult is not sustainable and that the maintenance of the populations of V. aff. sincorana depends on the survival of individuals, mostly adults. In general, we find evidence that the conservation of V. aff. sincorana and its management for extractive purposes depend on periodic fire occurrence.